Structure Damage on Cotton Fiber via Coupling Effect of Moisture Regains and Low Temperature - Jiqiang Cao; Xiang Liu; Ruolian Mo; Hongling Liu; Hong Xu (Journal of Natural Fibers)
The most crucial variables that influence the characteristics and quality of cotton fibers during the cotton growth and ginning processes are temperature and moisture regains. Here the cotton fiber samples were generated with pre-treatment using a synergistic strategy of moisture regains and low temperatures, the morphology and structure of the fibers with different pre-treatments were analyzed by using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray Photoelectron Spectrometer (XPS), X-ray diffraction (XRD), and Carbon-13 Nuclear Magnetic Resonance Spectrometry (13C NMR). Further, the mechanical properties of the cotton fibers were evaluated using LLY-06E tensile. The results shown that, with 3 days of freezing in -18℃, the linear density variation of the cotton fiber samples reached maximum, and the surface of the fibers showed noticeable fractures, local holes, and folded damage. Moreover, the low temperature and high moisture regain caused the internal water molecules of the cotton fibers interact in complex ways, altering the intermolecular forces but without changing the chemical composition. This research expands the temperature field of cotton fibers, particularly in the ginning process, by investigating the damage to the mechanical characteristics of cotton fibers caused by the combined effect of low temperature and moisture regain.